SANKSI TINDAK PIDANA KORUPSI DALAM PERSPEKTIF FIQIH JINAYAT - M. Wahib Aziz (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2016)
Islamic Shari'ah functioned by God as a deterrent to evil. Jurisprudence of Jinayat in Islamic law recognizes three kinds of punishment for a crime committed by a person; Qishah, hudud and ta'zir. The determination of punishment is not merely a revenge, but rather a goal to create a deterrent effect or shock to create a calm and peaceful society situation as the message contained in the word hayah which means a peaceful life. This paper aims to reveal the concept of punishment in the crime of corruption in the eyewear of Jinayat jurisprudence. Through literature review it can be concluded that the sanction of corruption is ta'zir, which is adjusted with the judge's decision based on the level of corruption that has been done. Sanctions in the form of ta'zir vary from mild to severe enough to recall corruption with a complex social impact. The ta'zir sanctions that can be given to the perpetrators of corruption are; Imprisonment, defamation, material fines to death penalty.—Syariat Islam difungsikan Allah sebagai pencegah kejahatan. Fikih Jinayat dalam syariat Islam mengenal tiga macam hukuman atas kejahatan yang telah dilakukan oleh seseoorang; qishah, hudud dan ta'zir. Penetapan hukuman tidak hanya sekedar pelampiasan dendam, namun lebih pada tujuan untuk menimbulkan efek jera atau shock terapy agar tercipta situasi masyarakat yang tenang dan damai sebagaimana pesan yang terkandung dalam kata hayah yang artinya kehidupan yang damai. Tulisan ini bertujuan untuk mengungkap konsep hukuman dalam kejahatan korupsi dalam kacamata fikih Jinayat. Melalui kajian literature dapat disimpulkan bahwa sanksi tindak pidana korupsi adalah ta’zir, yaitu disesuaikan dengan keputusan hakim berdasarkan kadar korupsi yang telah dilakukan. Sanksi berupa ta’zir ini beragam dari yang ringan hingga yang cukup berat berat mengingat korupsi membawa dampak sosial yang kompleks. Sanksi ta’zir yang bisa diberikan kepada para pelaku korupsi adalah; penjara, pencelaan, denda materi hingga hukuman mati.